Microalgae-Based Hybrid Biophotoelectrode for Efficient Light Energy Conversion - Silva, Caio C. G. [UNESP]; Martins, Guilherme; Luís, André; Rojas-Mantilla, Hernán D. [UNESP]; Rovisco, Ana; Martins, Rodrigo; Fortunato, Elvira; Pereira, Inês A. C.; Zanoni, Maria V. B. [UNESP]; Garrido, Saulo S. [UNESP]; Conzuelo, Felipe (American Chemical Society (ACS), 2025)
Photosynthetic microorganisms are promising candidates for sustainable energy production in photobio-electrochemical systems. However, integrating them with electrodes is challenging due to the compartmentalized nature of photosynthetic organelles. Microalgae, in particular, have a more complex cell structure than cyanobacteria, leading to low electron transfer rates and compromising electrochemical communication. In this study, we propose a hybrid biophotoelectrode that integrates intact microalgae cells with a WO3 semiconductor electrode using polydopamine for cell entrapment and charge transfer enhancement. The biophotoelectrode delivers photocurrents of up to 24 μA cm-2 under visible light illumination with an incident light power below 6.0 mW cm-2. The photoelectrode performance and the origin of electron flow are investigated, confirming a substantial contribution of immobilized microalgae to the overall photocurrent. We present a proof-of-concept application of the microalgae-based hybrid electrode in combination with a formate dehydrogenase biocathode for the implementation of a biophoto-electrochemical cell for the conversion of CO2 to formate assisted by light. The system demonstrates the potential for coupling photosynthetic processes with bioelectrochemical conversion, achieving efficient and sustainable production of value-added chemicals. These findings advance our understanding of photosynthetic cell-electrode interactions in hybrid systems, offering insights for developing photobio-electrochemical devices and innovative conversion strategies for waste products.